Social Cognition in Suicidal Behavior in Psychosis: A Systematic Review - María Carcedo Herrero; Aina Sastre-Buades; Maria Luisa Barrigón (Behavioral Sciences, 2025)
Suicide is a major concern worldwide, especially in psychotic disorders that have an increased risk for suicidal behavior (SB). There are many well-established risk factors for SB in psychosis. Still, others, such as the domains of social cognition (SC)—the theory of mind, social perception, emotional processing, and attributional style—are unclarified. We aim to review evidence on SC and SB in psychosis and clarify their relationship, examining the differences between SC domains and the potential mediating variables in this relationship and proposing that worse performance in regard to SC is related to a higher risk of suicide. We searched databases for papers on SC and SB published between 2009 and 2024, resulting in the 18 articles included in this systematic review. Individuals with psychotic disorders and SB showed better emotional processing for basic emotional recognition—although they performed poorly on more complex tasks—and exhibited greater empathy within the affective theory of mind. Cognitive biases associated with attributional style and increased distrust as part of social perception were also found. Our findings cannot establish a relationship with the cognitive theory of mind. So, further studies are needed to integrate all domains of SC in longitudinal studies and examine the mediating variables of these relationships.